Monolithic aerogel photocatalysts: a review - Wan, Wenchao; Zhang, Ruiyang; Ma, Minzhi; Zhou, Ying (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Photocatalysis has been considered as one of the most promising technologies for solving environmental pollution and energy crisis. However, photocatalysts in the powder form usually suffer from the strong tendency to agglomerate and intricate operation for recycling, which significantly limit their practical application. In comparison, monolithic aerogel photocatalysts with their highly macroscopic operability and recoverability as well as impressive specific surface area have attracted tremendous attention in recent years. With the development of synthesis technology, the types of aerogel photocatalysts have broadened from traditional oxide and chalcogenide aerogels to the current composite aerogels. Meanwhile, their application has also spread from primary physical adsorption to the present photochemical reactions including environmental remediation and clean energy production. In this review, the different synthesis strategies and photocatalytic applications of aerogel photocatalysts have been discussed. We summarize the currently available synthesis methods and widespread applications of aerogel photocatalysts. In particular, we highlight recent developments for the assembling of aerogel photocatalysts by direct synthesis and grafting photocatalysts to aerogel supports, as well as updated applications on the removal of aqueous pollutants, water splitting and gas phase photocatalysis. Finally, we outline the challenges and potential advances associated with the aerogel photocatalysts for future scientific research and commercial applications. This review has summarized the recent developments of aerogel photocatalysts along with their fabrication strategies and photocatalytic applications.